On the role of the indifferent electrolyte LiCl in electrophoretic deposition of hydroxyapatite from 2-propanol dispersions. Issue 15 (15th November 2016) - Drdlik, Daniel; Slama, Martin; Hadraba, Hynek; Drdlikova, Katarina; Cihlar, Jaroslav
Abstract: In the present work, the effect of an indifferent electrolyte (LiCl) on the electrical conductivity of dispersions for the electrophoretic deposition (EPD) of thick layers (>1 mm) of hydroxyapatite (HA) with low surface roughness was studied. The indifferent electrolyte was added at concentrations of 0.10 and 0.25 g/L into dispersions, which contained HA particles, 0–21.25 wt% monochloroacetic acid (MCAA) and 2-propanol. The stability of the dispersions, which was determined by measuring the zeta potential, increased with the MCAA content in the dispersion (up to −31.4 mV). An addition of LiCl slightly reduced the stability of the dispersions but significantly increased their electrical conductivity. The increase in electrical conductivity caused the decrease in deposition rate during the EPD, which affected the deposition yields and deposit thickness. The relative density of the HA deposits increased with the MCAA content in the dispersion and further increased when 0.10 g/L of LiCl was added. Moreover, using a highly conductive dispersion, thick HA layers were deposited with low surface roughness and no surface cracks. An optimum content of indifferent electrolyte in the dispersion enables the preparation of relatively dense and thick (>2 mm) HA deposits with a low surface roughness (~3 µm) via EPD, which can be used in medical applications.